The Relationship between Knowledge and Attitude and Compliance with Pregnant Women Consuming Iron Tablets at Anutapura Hospital, Palu - Dhiastri Aulianingrum; Abd Hakim Laenggeng; Andi Reza Alief Chairin Nur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
There were 129 cases of anemia at Anutapura Hospital in Palu in 2018 due to the lack of compliance of pregnant women in consuming iron tablets during pregnancy. This study aimed to determine the relationship between knowledge and attitudes with maternal compliance in consuming iron tablets at Anutapura Hospital. This research is a quantitative study with cross-sectional study design. Sampling in this study using accidental sampling method to 65 respondents. Analysis of statistical test results in this study using the Chi-Square test with a value of Î± = <0.05. The results of this study indicate that there is a relationship between knowledge and compliance of pregnant women in consuming iron tablets with a p-value of 0.000 and attitudes of compliance with pregnant women consuming iron tablets with a p-value of 0.000. It is recommended for midwives, cadres in posyandu, as well as health workers in the health promotion sector, to conduct counseling on the pattern of consuming iron tablets to overcome nutritional problems, especially in pregnant women